Gestão pública de regiões do semiárido do nordeste e municípios do estado do Ceará: meio ambiente e gestão de riscos e resposta à seca - Lima, Kaliny Kélvia Pessoa Siqueira (2021)
The Brazilian northeastern semi-arid region suffers from great climatic influences and the poor distribution of rainfall in this region causes a cycle of scarcity of the resource over a significant period over a year, bringing socioeconomic consequences that are reflected in health, education, work, housing and public policies, characterizing this region as vulnerable. Given this reality, this research aims to analyze how public environmental management, at the municipal level, has worked on environmental policies for risk management in combating drought in the Sertão Sobral region of Ceará. Therefore, we carried out a descriptive research of the case study type, with a quantitative-qualitative approach. The study involves the Sertão Sobral Planning region, Ceará, as a scenario. Data collection took place from July/2018 to February/2021 through access to the MUNIC database. A set of indicators were extracted that constitute the survey Profile of Brazilian Municipalities, published by IBGE, reference year 2017, comprising the tabs "environment" and "risk management", data worked and organized into three dimensions: institutional dimension, dimension procedural and command and control dimension. Descriptive Statistics was used, with calculation of absolute and relative values displayed in the form of tables and graphs, as well as tables with the intention of deepening nuances of a qualitative order. Among the 66 variables investigated, through indicators for the construction of dimensional management indices, the results showed an average of 36% (II = 0.36) for the Northeast, 47% (II = 0.47) for Ceará and 38% (II = 0.38) for the Sertão Sobral Planning Region regarding institutional management, considering the indicators for the constitution of the Municipal Environment Council and Fund, partnerships to carry out or maintain actions in the environmental/drought area and competent risk and disaster management bodies; average of 25% (IP = 0.25) for the Northeast, 36% (II = 0.36) for Ceará and 31% (II = 0.31) for the Sertão Sobral Planning Region regarding the procedural management, contemplating indicators of regulation, capacity building, participation, sources of funds and payment and municipal actions to avoid or minimize the damage caused by drought and; average of 42% (ICC = 0.42) for the Northeast, 49% (II = 0.49) for Ceará and 46% (II = 0.46) for the Sertão Sobral Planning Region for command and management management. control that involves indicators of environmental impacts and/or processes/actions with the greatest occurrence and events caused in the year of drought with the greatest impact. Considering the methodologically investigated dimensions and classified as institutional, procedural and command and control; the Northeast, Ceará and Sertão Sobral have low environmental management planning and drought disaster risk management, observing the average results of the indexes. It is concluded that, despite the considerations presented, for the Northeast, the states of Bahia and Ceará; and for the state of Ceará, the Sertão Crateús, Sertão Canindé, Maciço de Baturité and Grande Fortaleza planning regions; and for the Sertão Sobral planning region, the municipalities of Cariré and Sobral showed the best indices for evaluating municipal environmental management.